High Serum Level of IL-17 in Patients with Chronic Obstructive Pulmonary Disease and the Alpha-1 Antitrypsin PiZ Allele - Pervakova, Margarita Y.; Mazing, Alexandra V.; Lapin, Sergey V.; Tkachenko, Olga Y.; Budkova, Anna I.; Surkova, Elena A.; Emanuel, Vladimir L.; Titova, Olga N. (Pulmonary Medicine, 2020)
Chronic obstructive pulmonary disease (COPD) is multifactorial disease, which is characterized by airflow limitation and can be provoked by genetic factors, including carriage of the PiZ allele of the protease inhibitor (Pi) gene, encoding alpha-1 antitrypsin (A1AT). Both homozygous and heterozygous PiZ allele carriers can develop COPD. It was found recently that normal A1AT regulates cytokine levels, including IL-17, which is involved in COPD progression. The aim of this study was to determine whether homozygous or heterozygous PiZ allele carriage leads to elevated level of IL-17 and other proinflammatory cytokines in COPD patients. Materials and Methods. Serum samples and clinical data were obtained from 44 COPD patients, who included 6 PiZZ, 8 PiMZ, and 30 PiMM A1AT phenotype carriers. Serum concentrations of IL-17, IL-6, IL-8, IFN-γ, and TNF-α were measured by the enzyme-linked immunosorbent assay (ELISA). All A1AT phenotypes were verified by narrow pH range isoelectrofocusing with selective A1AT staining. A turbidimetric method was used for quantitative A1AT measurements. Results. COPD patients with both PiZZ and PiMZ phenotypes demonstrated elevated IL-17 and decreased IFN-γ levels in comparison to patients with the PiMM phenotype of A1AT. Thereafter, the ratio IL-17/IFN-γ in PiZZ and PiMZ groups greatly exceeded the values of the PiMM group. Homozygous PiZ allele carriers also had significantly higher levels of IL-6 and lower levels of IL-8, and IL-6 values correlated negatively with A1AT concentrations. Conclusions. The presence of the PiZ allele in both homozygous and heterozygous states is associated with altered serum cytokine levels, including elevated IL-17, IL-17/IFN-γ ratio, and IL-6 (only PiZZ), but lower IFN-γ and IL-8.